Basal Cisternostomy for Severe TBI: Surgical Technique and Cadaveric Dissection - Giammattei, L.; Starnoni, D.; Messerer, M.; Daniel, R. T. (Frontiers in Surgery, 2022)
Introduction: Cisternostomy is emerging as a novel surgical technique in the setting of severe brain trauma. Different surgical techniques have been proposed with a variable degree of epidural bone work. We present here the surgical technique as it is currently performed in our Institution. Methods: Anatomical dissection of one adult cadaveric head, injected and non-formalin fixed was perfomed. A large right fronto-temporo-parietal craniotomy was accomplished. Extradural sphenoidal drilling till opening of the superior orbital fissure was performed. The microsurgical anatomy of basal cisternostomy was then explored. Results: A step by step description of the surgical technique, enriched with cadaveric and intraoperative images, was made. Conclusion: Basal cisternostomy is a promising surgical technique that does not necessarily include complex surgical maneuvers. Trained neurosurgeon can safely implement it in their clinical practice.